A survey on insecticide usage patterns in Jasmine crops in Tamil Nadu, India - Ashvani , K; Ganesan, K; Murugan, M; Suganthy, M; Soundararajan, R P; Ganga, M (Plant Science Today, 2025)
Jasmine (Jasminum spp.) plays an important cultural and economic role in India, with Tamil Nadu leading its production, contributing over two-thirds of the national output. The insecticide use pattern study explores how jasmine farmers across nine key districts in the state manage pest control, focusing on the types of insecticides they use and where they get their information. Based on field surveys with 170 farmers conducted between 2024-2025, the findings show that most growers (85.93 %) are marginal farmers with less than one hectare of land and 42 % have only a middle school education. Low-volume power sprayers were the most widely used equipment (71.48 %), pointing to a preference for efficient and easy-to-use tools. When it comes to insecticides, broad-spectrum and mixed compound products dominate in the jasmine crop. The most widely used insecticide was Spirotetramat + Imidacloprid SC (29.81 %), especially in Krishnagiri (46.15 %) and Coimbatore (40 %). Commonly used single-compound choices include Alphamethrin 10 % EC (10.60 %) and Imidacloprid 70 % WG (8.66 %). On the other hand, newer, potentially safer alternatives like diamides (1.78 %) and spinosyns (0.62 %) saw very limited use. Most farmers relied on local input dealers for guidance (51.86 %), while trained extension officials were rarely approached (8.14 %). Heavy dependence on familiar chemical solutions and culminating point the need for better outreach, education and access to safer pest management options to support the long-term sustainability of jasmine farming.